Neutronic modeling and calculation of the Nuclear Heating Reactor NHR-5 by the deterministic codes DRAGON5 & DONJON5. (December 2021) - El Yaakoubi, H.; Boukhal, H.; Erradi, L.; Chakir, E.; El Bardouni, T.; El Barbari, M.; Lahdour, M.; Ziani, H.; Arectout, A.; Makhloul, M.
Abstract: The main objective of this study is to assess the neutronic modeling and calculations of the nuclear heating reactor NHR-5. To this end, the neutronic parameters of NHR-5 reactor underwent a comparative and validation protocols/methods through the analysis of the finite multiplication factor k e f f and some neutronic parameters including D, ν Σ f, Σ a as well as the power and flux distributions, using the evaluated nuclear data libraries ENDF/B-VII.1, JEFF3.1 and JENDL4.0 based on 172 energy groups. In this study, the collision probability approach is used to simulate and calculate the neutronic parameters in NHR5 reactor using the deterministic core diffusion code DONJON5 and the lattice transport code DRAGON5. The group constants of the reactor components were produced by DRAGON5. The DONJON5 code was then used to calculate the effective multiplication factor, excess reactivity, and power and flux distributions by introducing these group constants. The results are compared to those of the experiment to validate the calculation scheme. The results of the simulations reveal that the computed neutronic parameters consistently produce reasonable and consistent results of flux and power distributions, excess reactivity and all other parameters when compared to the experiment values. Therefore, the reactor models of NHR5 developed by DRAGON and DONJON codes were good in predicting the effective multiplication factor as well as the studied neutronic parameters. In this study, we being able to show the potential validation of the reactor physics lattice transport code DRAGON5 and the core diffusion code DONJON5, as well as the nuclear data libraries ENDF/B-VII.1, JEFF3.1 and JENDL4.0. Highlights: Neutronic Modeling and calculations of the Nuclear Heating Reactor NHR-5. Validation of the deterministic transport code DRAGON5 and diffusion code DONJON5. Calculation and analysis of excess reactivity as well as the power and flux distributions by deterministic codes. To rely on DRAGON5 and DONJON5 codes for NHR-5 calculations. The good consistency of the results ensures that a thermal-hydraulic analysis will be performed for NHR reactor.